Enhancing EFL Students’ Speaking Skills through Digital Storytelling in Podcast Projects - Khoirunnisa, Rahma Arsila; Authar, Nailul; Basuki, Edi Pujo; Afandi, Mujad Didien; Aquariza, Novi Rahmania (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Speaking is widely recognized as one of the most challenging skills for learners of English as a Foreign Language (EFL). Many students experience difficulties in expressing their ideas orally due to limited opportunities for practice, anxiety about making mistakes, and a lack of confidence when communicating in English. These challenges often hinder the development of speaking proficiency in language classrooms. Therefore, innovative and engaging teaching strategies are needed to create supportive learning environments that encourage students to practice speaking more actively. This study investigates the use of digital storytelling through podcast projects as a pedagogical approach to enhance EFL students’ speaking proficiency. The research employed a qualitative design involving ten students from the English Education Department at Nahdlatul Ulama University Surabaya. The participants were engaged in a digital storytelling activity in which they created their own podcasts, beginning with the process of selecting a story topic, writing scripts, rehearsing their narration, and finally recording and sharing their storytelling podcasts. Data were collected through semi-structured interviews in order to explore students’ perceptions and experiences during the podcast project. The collected data were then analyzed using thematic analysis to identify key patterns and themes related to students’ speaking development. The findings of the study indicate that the use of digital storytelling in podcast projects contributed positively to students’ speaking abilities. Participants reported increased confidence when speaking English, improved fluency, and better pronunciation as a result of repeated practice during the recording process.